Analisis Strategi Pengembangan Usaha Komoditi Kemiri Lokal - Anwar, Arnita Damayanthi; Widyantari, Ineke Nursih; Simatupang, David Oscar Simatupang (Musamus University, 2019)
Merauke Regency is a candlenut production center in Papua Province with an area of ​​land and an ever-increasing amount of production. Candlenut area in 2009 was 114.50 Ha and in 2012 it increased to 207.00 Ha, which was followed by an increase in production by 50% between 2010 and 2012. This study aimed to identify the factors be strengths, weaknesses, opportunities, and threats and formulate development strategies. Purposive research area determination in Yanggandur Village, Sota District, Merauke Regency. The population consisted of 12 people consisting of candlenut farmers, traders, and the government where all populations were sampled. Sampling was done by Purposive Sampling. The data used are sourced from primary data and secondary data. Data analysis using the SWOT method. strengths: availability of land and hazelnut plants in large numbers, the involvement of families and local communities in the business, business activities can help the family economy of farmers, the activity of processing candlenut in the village, how to market the results have reached the traditional markets, the large number of candlenut which falls out every season, the quality of hazelnut produced is quite good. Weaknesses are: lack of adequate equipment in processing activities, lack of business capital, long distance to the location of plants (from community houses to gardens and hamlets) for candlenut harvest, low knowledge, and farmers' desire in cultivation activities, low application of the system management in business, lack of farmers 'skills in processing the candlenut, lack of farmers' ability to do marketing outside the village, transportation facilities that support marketing activities are not yet smooth, the durability (quality) of hazelnut produced is still low. Keywords: development strateg; candlenut commodity; SWOT analysis